The Obese Heart - Sanjay Kalra; Bhupinder Singh; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
Obesity has been described as a chronic metabolic disease, characterized by excessive adiposity.1 Most discussion about the consequences and complications of obesity revolves around metabolic dysfunction, such as dysglycaemia, dyslipidaemia and hypertension. There is also increasing awareness about ectopic adipose tissue deposition and its deleterious effects.2 Fatty liver, fatty pancreas and fatty kidneys are terms that are used frequently in clinical descriptions of the disease. In spite of the strong link between obesity and cardiac ill-health, the term ‘obese heart’ or ‘fatty heart’, however, has not found traction in medical literature. This may be due to the complexity of obesity’s impact on the heart. Continued...